”KALA” dalam Bahasa Arab: KAJIAN WAKTU KEBAHASAAN - Nasiruddin Nasiruddin (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
Grammatical category of tense is directly related to paradigm of verb. Wright declares that two categories of verb in Arabic namely mâdi and mudâri’ are identic to tense that expresses time of situation. This Research finds that Arabic, through its linguistics tool, can express time concept of human experience in the best manner. The linguistics tool can be categorized in four parts, that are: 1) grammatical categories, which expresses linguistics time through verbal inflection; 2) lexical grammatic, that has two types which are a) particle that has implication in temporal meaning of verb, and b) nawâsikh (auxiliaries ); 3) lexical elements; and 4) sentence context. This research does not only study about theory of linguistics time and proposes imaginative patterns as Tammâm did, or draws the source with data from Qur`an only as Bakrî did, or focus on concept of time expressing elements as Akrom and Habib did, or doesn't proof with enough data as Arsyad did, but this research also tries to study the problem with comprehensive view and give same attention to data source in fushâ al-turâts and fasîhah mu’âsirah. The elected data as corpus in this recearch are approached by general linguistics and qawâ’id nahwiyyah, and they are analized by theories of linguistic time, especially theories of temporality, aspect, modality, and actionality; and also analized by qawâ’id nahwiyyah, especially theories of semantic function of verba's form, temporal’s particles, nawâsikh, and utterance manner (khabariyyah:insyâ iyyah).